2024
DOI: 10.3390/f15020340
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Distribution and Driving Effects of Net Primary Productivity along an Elevation Gradient in Subtropical Regions of China

Bo Xu,
Zhongke Feng,
Yuan Chen
et al.

Abstract: Globally, forest ecosystems, especially subtropical forests, play a central role in biogeochemical cycles and climate regulation, demonstrating their irreplaceable function. The subtropical region of China, characterized by its unique forest ecosystem, complex terrain, climate heterogeneity, diverse vegetation types, and frequent human activities, underscores the importance of the in-depth study of its net primary productivity (NPP). This paper employs the eddy covariance–light use efficiency (EC-LUE) model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Climate change is the internal source of vegetation change, while human activities are the external reason [12,[23][24][25][26][27][28]. Our study elucidates the correlation between the annual average NPP size of varying land use typologies within the SDHP: woodland dominates, followed by farmland, grasslands, shrubberies, and other land categories (Figure 6b).…”
Section: Impact Of Human Activities On Npp Changesmentioning
confidence: 65%
See 2 more Smart Citations
“…Climate change is the internal source of vegetation change, while human activities are the external reason [12,[23][24][25][26][27][28]. Our study elucidates the correlation between the annual average NPP size of varying land use typologies within the SDHP: woodland dominates, followed by farmland, grasslands, shrubberies, and other land categories (Figure 6b).…”
Section: Impact Of Human Activities On Npp Changesmentioning
confidence: 65%
“…Related studies have confirmed that high temperatures have an inhibitory effect on vegetation growth and productivity [16,23,24,26]. Vegetation and productivity in China have been deeply affected by climate change [14,27]. These studies emphasize that climate change, especially precipitation and temperature, are important climate factors affecting vegetation cover, productivity, and spatiotemporal differences [16,22,28].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…C storage and C emissions are unique to tree species and age, type of soil, altitude, and slope, therefore these parameters vary between tropical, temperate, or boreal forests, as well as between natural and managed forests [5]. C storage variations with altitude are crucial in the context of global warming because of their association with temperature [10,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%